Multimodal transport networks - Simon Fuchs; Woan Foong Wong (Federal Reserve Bank of Atlanta, 2022)
The movement of goods from origin to destination takes place over multiple modes of transportation. Correspondingly, intermodal terminals play an important role in facilitating transportation over the multimodal network. This paper studies multimodal transport networks and their impact on infrastructure investments. We propose a tractable theory of transportation across domestic transportation networks with multiple modes of transportation by embedding multimodal routes into a spatial equilibrium model with endogenous stochastic route choice. We calibrate the model to US domestic freight flows using high-resolution geographic information system information and detailed data on traffic along road, rail, and international ports. We estimate the strength of intermodal port congestion from ship dwell times and its multimodal impact on railcar dwell times. We then employ the model to evaluate the welfare effects of terminal investments across the United States. We identify important bottlenecks in the US transportation system, with the reduction of the transportation cost by 1 percent in the most important nodes generating welfare gains equivalent to US200-300 million of additional GDP (in 2012 USD).
Keywords: F11; R12; R42; 330; infrastructure investments; multimodal transport; spatial equilibrium